The R-functions method in mathematical modeling of convective heat transfer in fuel cartridge with fuel rods - Maksimenko-Sheyko, K.V.; Uvarov, R.A.; Sheyko, T.I. (Вопросы атомной науки и техники, 2013)
Conjugate boundary value problems of heat transfer in cases, when viscous incompressible fluid flows via channels of non-canonical sections, bypassing the bundle of rods, is considered. The influence of the packaging pattern on the velocity and temperature distribution is researched. The theory of R-functions in combination with the Ritz variational method were used for the solution. Different packaging of fuel rods are examined. Each package contains 91 rods, and the corresponding equations are constructed with the new design tools of the theory of R-functions.